Interrogating "the end, " becoming "the end". Issue 2 (3rd April 2022) - LeMaster, Lore/tta
ABSTRACT: For those of us for whom end times are marked by our arrivals, rhetorical threats of "the end" serve as discursive grounds out of which material experiences are animated. In our current hellscape, queer and trans folks are marked as cultural monstrosities across public and political discourses. Moved by the essays constituting this themed issue, I proffer a response by turning to the ways rhetorics of "the end" and of "end times" are projected onto queer and trans bodies. After all, to be trans and gender expansive is to be and become the end—the end of white supremacy's clutch on sex, gender, and bodily comportment. This is an ending we demand in full.